Immunophenotyping of cerebrospinal fluid cells in ischaemic stroke. (8th February 2019) - Schulte‐Mecklenbeck, A.; Kleffner, I.; Beuker, C.; Wirth, T.; Hartwig, M.; Schmidt‐Pogoda, A.; Klotz, L.; Hansen, W.; Wiendl, H.; Meuth, S. G.; Gross, C. C.; Minnerup, J.
Abstract : Background and purpose: Post‐ischaemic immune cell invasion into the brain is well characterized in animal stroke models and contributes to neuronal damage. Therefore, it represents a promising therapeutic target. Cerebrospinal fluid (CSF) is easily accessible and may reflect cellular events within the parenchyma. However, comprehensive studies on CSF immune cells in patients with stroke are lacking. Methods: In a retrospective cohort study, we performed extensive immune‐cell profiling in CSF and peripheral blood of patients with acute ischaemic stroke and healthy controls. In patients with stroke, infarct size was quantified on follow‐up imaging. Results: Overall, 90 patients with ischaemic stroke and 22 controls were included in our study. After stroke, the total protein was increased (537.3 vs. 353.2 mg/L, P = 0.008) and the mean total white cell count was slightly but non‐significantly elevated (1.76 vs. 0.50 cells/μL, P = 0.059). Proportions of CSF lymphocytes, monocytes and granulocytes and their respective subsets did not differ between patients with stroke and controls. In addition, there were no associations between proportions of major leukocyte subsets in CSF and the time from symptom onset to CSF sampling, infarct size or infarct localization. Conclusions: Ischaemic stroke induces only a very slight increase of CSF immune cells without changes in the composition of immune cell subsets, thus indicating that parenchymal inflammation is not sufficiently reflected in the CSF. Our findings suggest that CSF is not a major invasion route for immune cells and that CSF cell analyses are not suitable as biomarkers to guide future immune therapies for stroke.